Total, added and free sugar intakes, dietary sources and determinants of consumption in Portugal: the National Food, Nutrition and Physical Activity Survey (IAN-AF 2015-2016) - Marinho, AR (2020)
Objective: To assess total sugar (TS), added sugar (AS) and free sugar (FS) intakes, dietary sources, adherence to recommendations and determinants of consumption, in a Portuguese national sample. Design: Cross-sectional study. Dietary assessment was obtained by two food diaries in children aged <10 years and two non-consecutive 24 h recalls for other age groups. TS, AS and FS intakes were estimated by using SPADE software. TS content in food was estimated at the ingredient level. AS content in food was assessed through a systematic methodology and FS was based on the WHO definition. Setting: National Food, Nutrition and Physical Activity Survey (IAN-AF 2015–2016), Portugal. Participants: Representative sample from the Portuguese population, aged from 3 months to 84 years (n 5811). Results: Mean daily intake and contribution to total energy intake (E%) were 84·3 g/d (18·5 E%) for TS, 32·1 g/d (6·8 E%) for AS and 35·3 g/d (7·5 E%) for FS. Of the population, 76 % adhered to the FS recommendation (FS < 10 E%). The lowest adherence was in children (51·6 %) and adolescents (51·3 %). The main dietary source of TS was fruit across all ages, except in adolescents which was soft drinks. In children, the main dietary sources of FS were yoghurts and sweets, soft drinks in adolescents and table sugar in adults/elderly. FS intake was lower in children with more educated parents and in adults who practised physical activity regularly, and higher among smokers. Conclusions: Interventions ought to be planned towards decreasing intakes of added and free sugars considering population-specific characteristics.